Approaches to ensure an equitable and fair admissions process for medical training - Ngozi F. Anachebe; Leila Amiri; Kristen Goodell; Demondes Haynes; Remo Panaccione; Aaron Saguil; Carol A. Terregino; Mike Woodson; Kenneth Royal (Communications Medicine)
There has been considerable discussion of how best to address racial and ethnic disparities in health outcomes, both globally and specifically in the United States. Increasing diversity among future clinicians and physician-scientists has been identified as a key strategy for addressing and correcting health disparities among underrepresented populations. Increasingly, medical schools, the institutions that train clinicians, have embraced the practice of holistic review for evaluating applicants and virtually all medical schools have reported contributing to a diverse physician workforce as an important aspect of their educational mission. Yet despite these goals and practices, relatively little progress has been made in diversifying the workforce and achieving equitable health outcomes. Here we present a framework for centering equity in medical school admissions that focuses on equity-based recruiting, admissions standards, selection and support and present a number of promising examples and universally applicable strategies that medical schools can potentially implement given their unique missions, goals, priorities, and resources.